A novel sensitive and selective electrochemical sensor based on molecularly imprinted polymer on a nanoporous gold leaf modified electrode for warfarin sodium determination. Issue 49 (3rd May 2016) - Li, Yingchun; Zhang, Lu; Liu, Jiang; Zhou, Shu-Feng; Al-Ghanim, Khalid Abdullah; Mahboob, Shahid; Ye, Bang-Ce; Zhang, Xueji
Abstract : A novel electrochemical sensor was facilely fabricated by coupling nanoporous gold leaf (NPGL) with molecularly imprinted polymer (MIP), and afforded ultrasensitive and selective determination of warfarin sodium (WFS). Abstract : Warfarin sodium (WFS) is a widely used oral anticoagulant drug but has a narrow therapeutic window. Since traditional detection methods applied for therapeutic drug monitoring suffer some shortcomings, including difficulty in obtaining timely reports, high costs and tedious operation, it is necessary to develop a detection system for the rapid monitoring of WFS in biological samples. Here we report a novel electrochemical sensor, which was facilely fabricated by coupling nanoporous gold leaf (NPGL) with molecularly imprinted polymer (MIP) to afford ultrasensitive and selective determination of WFS. The morphological characterization via scanning electron microscopy proved the successful modification of the sensor by NPGL followed with MIP layer modification. The influencing parameters including the type of monomer, pH and molar ratio of template to monomer were optimized during electro-polymerization. Using Fe(CN)6 3−/4− as a probe acting as an electrical indicator, a linear relationship of the current response versus the concentration of WFS was obtained in the range from 1.0 × 10 −10 to 8.0 × 10 −8 M under the optimal experimental conditions, with a detection limit of 4.1 × 10 −11 M (S/N = 3). In addition, the as-prepared sensor exhibited specific detection of WFS over its structural analogues and interferents, and the established electrochemical approach was validated using the standard method – high performance liquid chromatography. Eventually, rapid and accurate determination of WFS in human blood was carried out after easy sample pretreatment.